2012
DOI: 10.3390/s120911505
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Paper-Based Sensors

Abstract: Paper-based sensors are a new alternative technology for fabricating simple, low-cost, portable and disposable analytical devices for many application areas including clinical diagnosis, food quality control and environmental monitoring. The unique properties of paper which allow passive liquid transport and compatibility with chemicals/biochemicals are the main advantages of using paper as a sensing platform. Depending on the main goal to be achieved in paper-based sensors, the fabrication methods and the ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
389
0
9

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 594 publications
(399 citation statements)
references
References 76 publications
1
389
0
9
Order By: Relevance
“…Detection has mainly been carried out using colorimetric assays for off-site analysis via the ubiquitous smartphone [9,10]; however, electrochemical detection has also been investigated [11,12]. Several reviews are available [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Detection has mainly been carried out using colorimetric assays for off-site analysis via the ubiquitous smartphone [9,10]; however, electrochemical detection has also been investigated [11,12]. Several reviews are available [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…4,5 μPADs have shown promise for their use in point-of-care testing during bioanalysis, as described in many publications. [6][7][8][9][10][11][12][13][14][15][16] When used in environmental analysis, μPADs have been successfully applied to the measurement of metal ions in particulate matters (PMs), [17][18][19] as well as being useful for measuring the oxidative activity of PMs.…”
Section: Introductionmentioning
confidence: 99%
“…31 For colorimetric sensing, analyte flow is directed along the paper matrix by capillary action, and the analyte then reacts with a label or an organic dye in the test zone. 32 The choice for this quinoxaline derivative was based on previous work from our research group in which naked-eye and UV-Vis analyses showed AAQX selective for the Cu 2+ detection in methanolic solution against several other cationic species. 33 In this context, as a subsequent step, we aimed to investigate the possibility of selective response to Cu 2+ when this compound is coated on paper.…”
Section: Introductionmentioning
confidence: 99%